Design and Development of DC to AC Inverter - Nur Fairuz, Mohamed Yusof
This thesis describes the design and construction of a Single Phase Full Bridge Inverter with Sinusoidal Pulse Width Modulated (SPWM) switching scheme. The design of inverter consists of four parts which are control circuit, gate driver circuit, power circuit and LC filter. An analog type controller is used for generating the desired SPWM control signal. The analog controller consists of triangular wave generator and sine wave generator. Triangular wave is generated by using combination of Schmitt trigger and integrator that is able to produce 12Vpeak to peak at 2.326kHz frequency. While the sinusoidal wave oscillator circuit is made up of phase shift, voltage follow and buffer and it produces an output sine wave at a frequency of 54 Hz. In gate driver circuit, HCPL-3020 is employed to drive the SPWM signal to the power switching circuit. While for the power circuit, four IGBTs are used as power switching devices. The complete circuit is simulated in PSIM software using real values from hardware testing. The inverter circuit is also simulated using PSpice software to observe the overall performance of the circuit when supplied an input voltage of 310VDC. The simulation results confirm the good operation of the inverter circuit. Besides that, hardware prototype of inverter is also implemented and tested.